(untitled) (PERcursos Linguísticos, 2020)
Guided by the Butlerian performative perspective, the article debates the role that language assumes in the production of bodies, discourses and resistance practices. With attention to the relations of knowledge-power-subjectivity implied in social practices, and to the concepts of performance / performativity, it is argued that this non-essentialist view contributes to densifying debates and analyzes of contemporary social / linguistic contexts.